Impact of maternal education on the development of severe acute malnourished children - Jain, Vaishali; Agrawal, Avyact; Shivangi Tomar,; Akhilendra Singh Parihar, (Asian Journal of Medical Sciences, 2024)
Background: Severe acute malnutrition (SAM) is a grave form of undernutrition that has been recognized as a medical and social disorder. Various factors contribute to the development of SAM, but the impact of maternal education on the nutritional status and development of the child is of paramount importance since focused interventions in this aspect can yield promising results. Aims and Objectives: The aims and objectives of the study are to assess the impact of maternal education on the development of children with SAM. Materials and Methods: A total of 125 SAM children in the age group 12–30 months were enrolled in this prospective observational study from among those admitted to the nutritional rehabilitation center of a tertiary care center in central India. The developmental status of SAM children was assessed using the Developmental Assessment Scale of Indian Infants. The association of maternal education with the development of SAM children was analyzed. Results: Overall developmental delay was observed in 44.8% of SAM children, whereas motor and mental development delay was noted in 45.6% and 44% of SAM children. The maternal education level was significantly associated with the overall development of the SAM child. (P=0.043 for motor development, P=0.017 for mental development, P=0.023 for motor developmental delay). Conclusion: Maternal education plays a key role in improving the developmental status of SAM children, who are more prone to developmental delays across various domains. Efforts toward enhancing maternal education, especially knowledge regarding child nutrition and development, can reduce the incidence and improve the management of SAM in children.